Witnessing the witness of war crimes, mass murder, and genocide from the 1920s to the present - Consonni, Manuela; Nord, Philip G. 1950- (De Gruyter Oldenbourg, 2023)
Rethinking the concepts of "witnessing" and "witness" is highly relevant to the study of war crimes, mass murder and genocide. Through multiple readings, the volume shows the meanings and functions of witnessing in a political and historical context marked by the emergence of multiculturalism. The ultimate goal is the exploration of divergent and intersectional positions of the witness and witnessing as both concrete and hermeneutical categories. As a result, the mechanisms of social, political, and psychological oppression, murder and genocide will become tangible and understandable with greater precision and finesse
Keywords: Geschichte 1920-2023; Gedächtnis; Kriegsverbrechen; Völkermord; Zeugnis; Augenzeuge; Massenmord; Aufsatzsammlung